Language conflict in the literary discourse: Jia Pingwa’s novel “Qin Qiang” - Alexander V. Ignatenko (Слово.ру: балтийский акцент)
The present study addresses the interdisciplinary issue of conflict and its linguistic specificity as a component of the emotive dimension in artistic discourse, with a focus on the novel “Qin Qiang” by Jia Pingwa (2005). The aim is to analyse the aspects of speech and language conflict, as well as its destructive forms, within the lexico-semantic, syntactic, and functional-stylistic units of the language. A conflictual communicative act is viewed as the result of specific failures in speech interaction and the violation of conventions and rules governing discursive behaviour. Linguistic contradictions and conflicts are analysed within the framework of emotiology, at the level of emotivity and the emotive field in the pragmatic space of artistic discourse, as a multimodal phenomenon shaped by systemic relations of emotionalism. Discursive contradictions function as key elements of the structural tension in the text, serving as linguistic and semantic dominants or attractors. These contradictions materialize as stylistic units at various levels and can be employed as a tool to create the desired effect in artistic narrative. Linguistically, conflict arises from violations of pragmatic-semantic and stylistic-syntactic conventional norms. Drawing on empirical material, the study demonstrates that the use of conflictogenic discourse in prose is a distinctive feature of Jia Pingwa’s idiosyncrasy, integrating various communicative strategies. The findings provide a foundation for further research into speech collisions in Chinese fiction.